Clinical Holistic Medicine (Mindful Short-Term Psychodynamic Psychotherapy Complimented with Bodywork) in the Treatment of Schizophrenia (ICD10-F20/DSM-IV Code 295) and Other Psychotic Mental Diseases - Søren Ventegodt; Isack Kandel; Joav Merrick (The Scientific World Journal)
Clinical holistic medicine (CHM) has developed into a system that can also be helpful with mentally ill patients. CHM therapy supports the patient through a series of emotionally challenging, existential, and healing crises. The patient’s sense of coherence and mental health can be recovered through the process of feeling old repressed emotions, understanding life and self, and finally letting go of negative beliefs and delusions. The Bleuler's triple condition of autism, disturbed thoughts, and disturbed emotions that characterizes the schizophrenic patient can be understood as arising from the early defense of splitting, caused by negative learning from painful childhood traumas that made the patient lose sense of coherence and withdraw from social contact. Self-insight gained through the therapy can allow the patients to take their bodily, mental, and spiritual talents into use. At the end of therapy, the patients are once again living a life of quality centered on their life mission and they relate to other people in a way that systematically creates value. There are a number of challenges meeting the therapist who works with schizophrenic and psychotic patients, from the potential risk of experiencing a patient's violence, to the obligation to contain the most difficult and embarrassing of feelings when the emotional and often also sexual content of the patient’s unconsciousness becomes explicit. There is a long, well-established tradition for treating schizophrenia with psychodynamic therapy, and we have found that the combination of bodywork and psychotherapy can enhance and accelerate the therapy and might improve the treatment rate further.